ANALISIS PENGARUH STRATEGI CO-BRANDING, HARGA PRODUK, DAN MEDIA SOSIAL SEBAGAI MEDIA PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK SEPATU LOKAL AEROSTREET DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING - Tahjuddin Ihsan Ashrori; Suryono Budi Santosa (Diponegoro Journal of Management, 2023)
ABSTRACT The research conducted this time has the aim of analyzing the influence of cobranding strategy, product prices, and social media as promotional media on purchasing decisions for local Aerostreet shoe products with buying interest as an intervening variable. The population used is consumers who buy local Aerostreet shoe products who are domiciled in Jakarta with ages 14-40 years. The sample used amounted to 151 respondents. The data collection method uses a questionnaire with the Structural Equation Modeling (SEM) analysis technique using AMOS 23.0 as an analytical tool. The results showed that co-branding had a positive and significant effect on purchase intention, price had a positive and significant effect on purchase intention, promotion had a positive and significant effect on purchase intention, and purchase intention had a positive and significant effect on purchasing decisions.